2019
DOI: 10.3390/app9112250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aggregate Micro Fines (AMF), Aluminum Sulfate and Polypropylene Fiber (PPF) on Properties of Machine-Made Sand Concrete

Abstract: With the depletion and increasing demand of river sand, machine-made sand could be used more and more in concrete. In order to improve the properties of machine-made sand concrete, the effects of the aggregate micro fines (AMF) content, aluminum sulfate, and polypropylene fibers (PPF) on the slump, compressive strength, water permeability, and the chloride permeability coefficients were investigated through a single factor test method, and related mechanisms were analyzed. The results show that the optimum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 48 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Additionally, it’s working state and mechanical properties in engineering structural components are worth exploring in depth [ 33 , 34 ]. In addition, due to the large quality fluctuations in the production process of machine-made sand, there are fewer studies on the effect of machine-made sand quality on the performance of concrete [ 35 ]. Therefore, further research is needed on the effect of quality variation of machine-made sand of different lithologies on performance.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it’s working state and mechanical properties in engineering structural components are worth exploring in depth [ 33 , 34 ]. In addition, due to the large quality fluctuations in the production process of machine-made sand, there are fewer studies on the effect of machine-made sand quality on the performance of concrete [ 35 ]. Therefore, further research is needed on the effect of quality variation of machine-made sand of different lithologies on performance.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [49], the machine-made sand concrete (MSC) indicated an increase in its compressive strength at low content levels of aggregate micro fines (AMF); then, the strength decreased with a further increase in AMF content. Conversely, the AMF content evinced the opposite effect on the chloride and water permeability coefficients of the MSC.…”
Section: Introductionmentioning
confidence: 93%
“…The addition of nanoparticles to cement-based composites is a new trend due to their increasing availability on the market and knowledge concerning their manufacturing [11][12][13]. The authors in [14] performed studies on overlays with the addition of amorphous silica nanospheres.…”
Section: Fig 2 Scheme Of Pores Formation After Mortar Bleeding Witmentioning
confidence: 99%